Firm's Value Exploration: The Impact Of Intellectual Capital and Net Working Capital - Lestari, Beti Dwi; Suryani, Ani Wilujeng (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2020)
Intellectual capital (IC) gains more importance nowadays, and hence, this study investigates the impact of IC and net working capital (NWC) on firmsÃ¢â‚¬â„¢ values creation. If IC has a greater impact than NWC, it indicates that automotive and components companies in Indonesia have paid attention to IC's contribution to increase company value. This studyÃ‚Â wasÃ‚Â conducted on 15 automotive and componentsÃ‚Â companiesÃ‚Â from 2011 to 2018Ã‚Â as thisÃ‚Â industryÃ‚Â utilises more IC and NWC thanÃ‚Â anyÃ‚Â other industries. We used panel data regression analysis with random effectÃ‚Â modelÃ‚Â to test the hypothesisÃ‚Â of 92 data, with IC calculated through theÃ‚Â MVAIC model, andÃ‚Â firmÃ¢â‚¬â„¢sÃ‚Â value is measured by TobinÃ¢â‚¬â„¢s Q. The results show that IC has no significant effect on firmsÃ¢â‚¬â„¢ value. Meanwhile, NWC has a significant negative effect on firmsÃ¢â‚¬â„¢ values creation.Ã‚Â These important findings suggest thatÃ‚Â automotive and componentsÃ‚Â firms shouldÃ‚Â apply strategic management in managing IC and NWC to increase the firmÃ¢â‚¬â„¢s value.Ã‚Â